TIGER SHRIMP (Penaeus monodon) GROWTH AT DIFFERENT STOCKING DENSITIES IN HIGH SALINITY POND USING MANGROVE RESERVOIR - Gunarto Gunarto; Muslimin Muslimin; Muharijadi Atmomarsono (Indonesian Aquaculture Journal, 2006)
High salinity pond water ranging from 33—45 ppt between July and October is one of the problems occurred in western part of South Sulawesi brackishwater ponds. It is necessary to know if tiger shrimps grow well in such salinity, since the optimum salinity range for the growth of tiger shrimp is 15—25 ppt. The objective of the research is to know the tiger shrimp production at different stocking densities cultured in high salinity pond in mangrove reservoir. Twelve pond compartments of 500 m2 each were arranged randomly for three treatments of shrimp stocking densities i.e. 4 ,  6, and 8 pcs./m2 , where each treatment was in three replications. The result of study showed that shrimp production at 6 pieces/m2 was higher than that of 4 and 8 pieces/m2, with more efficient  feed conversion was obtained in this stocking density (1.3) compared to treatment 4 pieces/m2 (1.5) and treatment 8 pieces/m2 (>3).